Evaluation of micronuclei in oral squamous cell carcinoma and potentially malignant disorders via different staining techniques - Khan, Mohammad Imran; Khare, Abhisheik; Khan, Sameera Shamim; Arif, Khushboo; Nasir, Abdullah; Lari, Shafik (Publishing Office of the University of Rzeszow, 2024)
Introduction and aim. Oral squamous cell carcinoma (OSCC) and premalignant disorders (PMDs) are becoming common in India as the use of tobacco in different forms is increasing from a young age, and the prevalence of this disease is becoming more common in middle age. Identifying disease at earlier stages is an important measure for limiting disease incidence and improving patient prognosis. The micronuclei count can be a valid biomarker for screening suspected patients and can be helpful in educating patients about the discontinuation of treatment, diagnosing the disease in its early stages and planning a treatment for a better prognosis. Different stains that are nuclear specific can be used to identify micronuclei. The aim was to establish diagnostic efficacy of various staining techniques in OSCC and potentially malignant disorders on oral brush cytology smears with observation of micronuclei as a valid biomarker for evaluation of the disease. Material and methods. Exfoliative cytology was done with oral brush and smears are obtained from 25 oral squamous cell carcinoma, 25 leukoplakia, 25 lichen planus, 25 oral sub mucous fibrosis patients and 15 samples with no disease. Each smear was stained with five different stains Papanicolaou (PAP), hematoxylin and eosin (H&E), toluidine blue, Leishman and Giemsa (LG) cocktail and Feulgen and observed for staining efficacy of micronuclei and cellular structures. Results. The best stain to observe DNA content as micronuclei is Feulgen which gives clear and crisp details of micronuclei without giving any false count as it is nuclear specific stain. PAP can be the second choice stain. Micronuclei count is definitely increased in OSCC and PMDs compared to samples without disease confirming its use as biomarker. Conclusion. Micronuclei count in oral brush cytology smears is a valid biomarker for evaluation of premalignant disorders and OSCC and can be used for detection of disease in individuals and for screening purposes of large populations at risk. Feulgen stain is best to study DNA content as micronuclei, on the other hand PAP can be used in large sampling investigations where there is lack of armamentarium.
The duly constituted Ethical Committee for Post Graduate students of Career Post Graduate Institute of Dental Sciences & Hospital, Lucknow has approved and cleared the research project (ethical ref. No. CPGIDSH/22/280).
Keywords: Feulgen stain; micronuclei; oral squamous cell carcinoma; potentially malignant disorders